Punching shear in flat slabs with re-entrant corner columns - João Paulo de Almeida Siqueira; Aparecida Evangelista Cartaxo; Guilherme Sales Melo (Revista IBRACON de Estruturas e Materiais)
Abstract Studies on slab-column connections supported on re-entrant corners are limited. Although design standards generally provide detailed guidelines for internal, edge, and corner connections, re-entrant corner connections are overlooked in these standards. To investigate the structural behaviour of re-entrant corner connections, a model without shear reinforcement was tested and compared with an interior slab-column connection with similar characteristics. The results were analysed in terms of crack pattern, ultimate loads, rotations, strains at the concrete surface and strains in the flexural reinforcement. The ultimate loads were compared with values estimated from ABNT NBR 6118 (2023), ACI 318 (2019), and EN 1992-1-1:2004 (Eurocode 2). In addition, remarks on the calculation models for slabs supported on re-entrant corner columns were provided. The mean of the ratio of experimental to theoretical results of EN 1992 and ABNT NBR 6118 equations was found to be more accurate than those of ACI 318 predictions.